Introduction to management - DuBrin, Andrew J. (Andover, Mass. : Cengage Learning Asia Pte Ltd, 2012)
Introduction to management is written for newcomers to the field of management and for experienced managers seeking updated information and a review of fundamentals.
Part 1 : Introduction to management -- Part 2 : Planning -- Part 3 : Organizing -- Part 4 : Leading -- Part 5 : controlling -- Part 6 : Managing for personal effectiveness
Includes index.
Keywords: MANAGEMENT